Equações do segundo grau: uma abordagem investigativa - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work is the consolidation of a research that proposed to analyze the use of technologies and the application of scenarios for research in solving the equations of the second degree. This research sought to understand how the use of research scenarios as a teaching methodology can favor the formation and development of critical thinking. For the development of the research, initially, it was suggested the application in an elementary school class, in which the studies of the equations usually start, but due to the restrictive measures imposed to reduce the contagion by Covid-19, it was chosen to apply in a group of Seminars from the Mathematics-Licentiate Course at the Federal University of Pampa. The data were collected from the application of two questionnaires and through participant observation during the moments of application of the practical activity. As a result, it is indicated that the research participants identified in the proposed activities the potential to constitute an activity with a scenario for investigation. In addition to this aspect, it is pointed out that the use of technologies and the application of investigative methods goes through the transformation of thinking regarding teaching methods, which are used from the training of teachers to arriving in the classroom.
Keywords: Investigação Matemática; Cenários para investigação; Tecnologias; Equações do segundo grau; Mathematics Investigation; Scenarios for investigation; Technologies; Second degree equations; CNPQ::CIENCIAS EXATAS E DA TERRA